Positron profiles and positron annihilation in thin layers - Pogrernyak A. D. (1982, 1982)
The moderated positron density distribution over the sample depth is properly calculated. The results obtained are used as the basis for the positron annihilation probability in thin foils and surface layers. The annihilation photon angular distribution (APAD) for the double-layer samples is measured. Using the results obtained the minimum foil thickness of materials of various effective atomic numbers on the semiconductor GaAs support is determined. Their structure can be studied by the positron-spectroscopy method with the 22Na(ß+, γ) emitter.